Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) Associated with Mycoplasma pneumoniae Infection - Guy Shalom; Raed Khoury; Amir Horev (Karger Publishers, 2020)
Mycoplasma infection may lower the threshold for drug allergy in particular patients. We present a case of drug reaction with eosinophilia and systemic symptoms (DRESS), with drug etiology and non-drug etiology (Mycoplasma infection). Possible synergism between previously known drug allergy and the acute Mycoplasma infection may have led to DRESS eruption. Interferon-γ release test and TNF-α release test yielded different patterns in the present case, suggesting a different role for each in different drug eruption types.